Music Accompaniment Of Japin Carita South Kalimantan (Universitas Negeri Semarang, 2021)
This research was conducted due to the lack of public knowledge about the music accompaniment of Japin Carita from South Kalimantan. This research focused more on the theory and practice of music science regarding the music accompaniment of this local South Kalimantan theater. This research used naturalistic qualitative method because it was held in natural conditions (natural setting), this method is also called the ethnographic method. Data gathering techniques include; observation, interview, documentation. Data analysis techniques include data reduction, data presentation, and verification. Japin Carita is a traditional theater art from South Kalimantan which is derived from the art of Japin, a dance that originates from Arab. The word Japin in Arabic originating from the word zafin which means fast footwork, and just like the definition Japin dance movement is indeed prioritizing foot movements. The structure of musical forms that can be used as music accompaniment to Japin Carita are; Gasim, Takzim, Rawis, Melagu, Nyanyian, and Tahtim. Japin music in Japin Carita theater is not only for the opening music, but also when the actors enter and leave the stage, and for the closing music. Music illustrations depicting the atmosphere of a place or the mood of an actor, whether sad, afraid, anxious, happy and so on must also follow the rhythm of Japin music. Japin Carita musical instruments consist of baboons, gongs, violins, keprak, and gambus. The function of Japin music accompaniment includes entertainment media, communication media, symbolic tribute, physical responses, continuity media, cultural statistics, and atmosphere proponent of the Japin Carita play/ script.